2011
DOI: 10.1002/anie.201105111
|View full text |Cite
|
Sign up to set email alerts
|

Giant Dielectric Anomaly of a Metal–Organic Perovskite with Four‐Membered Ring Ammonium Cations

Abstract: Ferroelectric materials with dielectric constants larger than 10 4 over a broad temperature range near room temperature have great potential for technological applications. Such highly polarizable materials have been found only in the perovskite-related metal oxides called relaxors. [1][2][3] Recently, the development of molecule-based highly polarizable materials has attracted increasing interest. For example, antiferroelectric and ferroelectric porous coordination polymer crystals with guest water molecules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 19 publications
4
57
0
Order By: Relevance
“…The compounds with the azetidinium (four-membered ring ammonium) ion, [(CH 2 ) 3 3 ] (M = Mn, Cu, Zn), have been reported to have extraordinarily large dielectric constants over a wide temperature range [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The compounds with the azetidinium (four-membered ring ammonium) ion, [(CH 2 ) 3 3 ] (M = Mn, Cu, Zn), have been reported to have extraordinarily large dielectric constants over a wide temperature range [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…7−18 Azetidinium metal formates ([CH 2 ) 3 NH 2 [M(HCOO) 3 ], AzM) with M = Mn, Cu, and Zn, crystallize in the orthorhombic structure with space group Pnma and undergo phase transitions into the monoclinic structures. 3,19,20 For AzZn, the transition occurs at 255 K to the P2 1 /c structure. 20 These compounds were also reported to exhibit giant dielectric anomalies.…”
mentioning
confidence: 99%
“…20 These compounds were also reported to exhibit giant dielectric anomalies. 19,20 Here it is important to note that AzZn is unique in the family of azetidinium metal formates because it shows the presence of an intermediate polar orthorhombic phase with space group Pna2 1 , stable between T c2 = 255 and T c1 = 300 K. 20 Although there is no confirmation that the Pna2 1 phase is ferroelectric, it was suggested that the dielectric properties of this material might be related to the formation of small ferroelectric domains near T c1 . 20 AzM compounds with M = Cu, Zn, and Mn have also attracted attention because of the high flexibility of their frameworks, which is advantageous for creating novel ferroelastics exhibiting large shear strains.…”
mentioning
confidence: 99%
See 2 more Smart Citations